Arteriovenous Shunt (AV Shunt) Sebagai Akses Hemodialisis Pada Pasien Chronic Kidney Disease (CKD): Arteriovenous Shunt (AV Shunt) Sebagai Akses Hemodialisis Pada Pasien Chronic Kidney Disease (CKD) - Abed Nego Okthara Sebayang (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2020)
Background: Arteriovenous Shunt (AV Shunt) is an anastomosis operation of an artery and vein in the arm or other body part with the aim of making the connection as hemodialysis access. AV shunt is the gold standard of creating vascular access for hemodialysis in patients with chronic kidney disease. AV shunt was created to increase the effectiveness of dialysis and reduce the risk and complications of other vascular access. Discussion: Based on its location, making the AV shunt has priority, namely the distal arm of the non-dominant arm. If this is not possible, AV shunt can be performed proximal to the non-dominant arm and finally to the proximal part of the dominant arm. The location of the wrist is a top priority in making AV shunt because it has many advantages. The arteries and veins that are commonly used are the radial arteries and vein cephalica and the brachial arteries with vein cephalica. Conclusion: AV shunt is the gold standard of creating vascular access for hemodialysis in patients with chronic kidney disease. . It is hoped that through the AV shunt action the life expectancy of patients with chronic kidney failure can increase and must be supported by other disciplines such as interna, psychologists and the patient's family.